Digitalization in Reading Classroom: How University Students View Digital Texts? - Nurjanah, Ratih Laily; Talenta, Pratama Irwin (Journal of Foreign Language Teaching and Learning, 2000)
Background: The implementation of digital texts in classrooms can be helpful yet coming with some issues faced by the students. The research gap targeted by this paper is related to how students view digital texts in terms of the implementation and how digital texts influence their reading comprehension. Objective: This paper aims to present how students perceived the use of digital text in a reading classroom. Methods: It was a case study involving 40 students of 4th semester as the respondents selected with purposive sampling technique to fill out a questionnaire distributed by the lecturer. 20 students of them were selected with snowball sampling as the respondents of interview.  The responses were analyzed with thematic analysis approach. Findings: The findings revealed that using digital texts mostly can be enjoyable for students since it is easy for them to bring the text in their smartphones though it comes with several problems such as eyes fatigue. It also revealed that students’ comprehension skill was not significantly helped by digital texts. Conclusion: The implication is presenting insights on how to manage the use of digital texts based on students’ perceptions.